Technological infrastructure for knowledge management - Ahmad, Abd Rahman; Mat, Norazuwa; Romli, Ruslan (2001)
Interest in the topic of knowledge management has undoubtedly boomed over the last few years.There are clearly organizational trends, which are aligned to this focus, and several initiatives were taken along the process.Besides that, technology is undeniable becoming a significant tool for gearing knowledge management in organizations.The consideration of technology led to the usage of technological infrastructure intensively.However, the knowledge management literature paid little attention on the issues and focusses on technology infrastructure.this paper attempts to study on the technological infrastructure used in the selected organizations in Malaysia.Eight technological infrastructures were identified such as Internet, Intranet, Document Management System (DMS),Groupware, Data Warehousing/mining, Decision Support Systems (DSS),Extranet and Unifying Messaging System (UMS) to be technological infrastructure for knowledge management.The results from the preliminary study are then shown in the descriptive form.Finally, the paper draws conclusion and suggestions for creating and sustaining knowledge management by using those technological infrastructures.